(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
Cultural institutions and businesses (CIBs) in Croatia are facing financial challenges due to the recent economic crisis and limited state support, as well as the growth of competition that is partially the result of the development of new technologies that have made culture more accessible on a global scale. For the purpose of filling the budget gap, CIBs are now forced to “step out” on the market trying to be more competitive in securing alternative sources of funding. The aim of this paper is to determine if CIBs have been successful in this endeavour, and to what level they use and understand the concept of alternative financing, as well to assess their ability and competence in raising funds from these alternative sources. The research was conducted by using a highly structured online questionnaire on a sample of public and privately-owned CIBs registered in Eastern Croatia and semi-structured, in-depth interviews with the CIBs executives. The research results showed that although the CIBs are to some extent using alternative sources of funding, these sources are underutilized and there is a recognized need for increasing the level of knowledge, employment of experts in the field of alternative funding in culture and introducing employee motivation models. The government was found to be one of the most important factors in conducting the activities aimed at providing preconditions, i.e. creating the regulatory framework, education, raising awareness, and motivation of CIBs for increasing the share of alternative sources of funding.